Formulation and Evaluation of Herbal Soap for Fairness and Glowing Skin - Nitisha Badwani, Aarti Nandwana, Archana Dubey, P. K. Dubey (International Journal of Pharmaceutical & Biological Archive, 2025)
Herbal soap is a type of soap made using natural ingredients derived from various herbs and plants. Herbs such as lavender, mint, rosemary, and chamomile are commonly used in making herbal soap. At present, a significant number of cosmetic products are adulterated, and numerous other beauty preparations available in the market are of inferior quality, posing potential risks of side effects such as skin rashes, allergic reactions, and even the development of skin diseases. Collection of the necessary ingredients: A high-quality soap base, such as caustic soda or coconut oil, is needed. The herbal ingredients, such as essential oils, dried herbs, and botanical powders, are collected. After melting the soap base, take it off the heat and incorporate the herbal ingredients by stirring them in dried herbs, essential oils, or powders are used. Add the herbs slowly and stir continuously to ensure they are evenly distributed throughout the soap. Once the herbs are added, pour the soap mixture into molds. Silicone molds or plastic containers coated with cooking spray are used. Let it cool and harden for hours or overnight. The study investigated the efficacy and consumer perception of a newly formulated herbal soap derived from natural ingredients, focusing on its cleansing properties and dermatological effects.